Pelatihan Pembuatan Ekoenzim dari Limbah Organik Rumah Tangga di Gampong Kopelma Darussalam, Banda Aceh - Chamzurni, Tjut; Jauharlina, Jauharlina; Sriwati, Rina; Mukhriza, Teuku; Oktarina, Hartati (Universitas Syiah Kuala, 2024)
Ecoenzyme is the result of fermentation of organic kitchen waste such as fruit and vegetable pulp, sugar and water. Ecoenzyme acts as various purposes such as pesticide and disinfectant. Therefore, we conducted community service activities aimed at providing a training in making ecoenzymes from household organic waste. Ecoenzyme-making training was given to the Family Welfare Development Group (PKK) in Gampong Kopelma Darussalam, Banda Aceh. The participants were lectured about ecoenzyme and its benefits and followed by discussion. It was then followed by a practical session on ecoenzymen-making activity. From this activity, the PKK group in Gampong Kopelma Darussalam, Banda Aceh, gained knowledge about a method to manage household organic waste become useful products. Furthermore, these skills can also be a source of additional income for local residents. During the training, the service team brought ready-made ecoenzymes and plants so they could provide examples of how to apply ecoenzymes to plants. The ecoenzyme and plants were given as souvenirs to the training participants.